Romanian Medical Students’ Attitude towards and Perceived Knowledge on COVID-19 Vaccination - Ana Bălan; Ioana Bejan; Simona Bonciu; Cristina Elena Eni; Simona Ruță (Vaccines, 2021)
In Romania, the first phase of the COVID-19 vaccination campaign prioritized medical personnel, which included healthcare students. This study aimed to assess their knowledge, attitudes towards, and perception of COVID-19 vaccination. An anonymous, single-answer, 42-item online survey was conducted from 12 January until 3 March 2021, in the country’s largest University of Medicine and Pharmacy. Among the 1581 respondents (14.9% response rate), 88.5% were pro-vaccination, 7.8% were undecided, and 3.7% were vaccine resistant. The main reason for vaccine rejection was the perceived speed of vaccine development (strong agreement among the vaccine resistant, moderate agreement among the undecided, p < 0.001). Concern over long-term adverse reaction was present in only 11.5% of the respondents, significantly more frequent in the undecided and vaccine resistant. Perceived knowledge on the vaccines’ safety, efficacy, and technology correlated with a pro-vaccine attitude (p < 0.001). Most respondents had a positive stance towards vaccination in general, influencing their behaviour as future parents (99.3% of the pro-vaccination, 95.1% of the undecided, and 89.1% of the vaccine resistant will vaccinate their children, p < 0.001) and as medical professionals (99.7% of the pro-vaccination, 93.5% of those undecided, and 89.8% of the vaccine resistant would advise parents to vaccinate their children, p < 0.001). Healthcare students can thus serve as important vectors for scientifically sound information, influencing vaccine uptake in the community.